Magneto-optical studies of magnetic defects in CeNiSn - Singleton, J; Hill, S; Ardavan, A; Matsui, H; Blundell, S; Hayes, W; Goy, P; Bucher, E; Hohl, H; Nakamoto, G; Menovsky, A; Takabatake, T (1996)
Millimetre wave magnetotransmission measurements are used to provide the first clear evidence for magnetic defects in CeNiSn. At least two defect configurations are observed, both probably involving Ce3+ ions.